The Effect of Nutrition Intervention With Oral Nutritional Supplements on Ovarian Cancer Patients Undergoing Chemotherapy - Qin, Nan; Jiang, Guichun; Zhang, Xu; Sun, Di; Liu, Meishuo (Frontiers in Nutrition, 2021)
Background: Chemotherapy is currently a common treatment for ovarian cancer, but the resulting side effects can exacerbate malnutrition. Our aim was to investigate the beneficial effects of oral nutrition supplements (ONS) on ovarian cancer patients undergoing chemotherapy. Methods: Single-blinded randomized controlled trial. Patients with ovarian cancer receiving chemotherapy were randomly assigned either to the ONS or non-ONS groups via a simple randomization. The ONS group was given 250 mL ONS each time (1.06 kcal, 0.0356g of protein per mL), three times a day, and nutrition education. Control group received nutrition education alone. The primary outcome was the nutritional status of the patients as assessed by the Patient-Generated Subjective Global Assessment (PG-SGA). The secondary outcome was the results of the participants' biochemical tests at each measurement time point. Data were collected (T0) at baseline, (T1) post intervention at 3 weeks, (T2) 9-week follow-up, (T3) 15-week follow-up. Generalised estimating equation models were used to compare the changes in outcomes over time between groups. Results: 60 participants (30 ONS, 30 controls) completed the trial, and data was analyzed. For baseline comparisons, no significant differences were found between the two groups. A progressive trend toward amelioration in PG-SGA scores over time was found within the ONS group, with scores decreasing from 9.27±1.68 at baseline (T0) to 5.87±2.06 after the intervention (T3). The number of patients with severe malnutrition also decreased from 19 (63%) at baseline to 4 (13%) and was statistically different at T3 compared to the control group. Furthermore, ONS group achieved a significantly greater reduction in PG-SGA score at the T1 (p = 0.03, confidence interval -2.23 to -0.11), T2 (p = 0.001, confidence interval -2.86 to -0.74) and T3 (p < 0.001, confidence interval -3.81 to -1.53), than the control group. In terms of biochemical test results, patients in the ONS group had better leukocytes, lymphocytes, Hemoglobin, Albumin and Total Protein than the control group at different time points, with statistical differences between the two groups (p < 0.05). Conclusions: The present study demonstrated that ONS can significantly improve the nutritional status of patients undergoing chemotherapy for ovarian cancer.